Biomass and energy transfer to baleen whales in the South Atlantic sector of the Southern Ocean - S Reilly; S Hedley; J Borberg; R Hewitt; Deborah Thiele; J Watkins; M Naganobu (2004)
Baleen whales are an important group of predators on Antarctic krill in the Southern Ocean. During the CCAMLR 2000 Survey to estimate the biomass and distribution of Antarctic krill, International Whaling Commission observers carried out a visual line transect survey to estimate the number of baleen whales occurring in the survey area. This paper reviews techniques used to estimate krill consumption by baleen whales and in combination with estimates of whale abundance estimates of krill consumption are generated for the South Atlantic sector of the Southern Ocean. This survey estimates that the present populations of whales feeding in this region are likely to consume approximately 1.6 million tonnes, but possibly up to as much as 2.7 million tonnes of krill within the summer season. Although this only represents 4–6% of the estimated krill biomass in the region (and probably less than this percentage of the total annual krill production), the depleted numbers of baleen whales resulting from past or current whaling activities should be taken into account when setting quotas for the commercial exploitation of krill if there is to be a recovery to pre-exploitation biomass levels of baleen whales.